Strategi Kepala Madrasah Dalam Peningkatan Pengelolaan Sarana Prasarana di MTs Yatashi Bogor - Kusumaningrum, Hesti; Syukur, Muhammad; Angga, Robi; Kardipah, Seipah (Peneliti.net, 2024)
Infrastructure management analysis strategy as seen from the analysis This SWOT research was carried out at MTs Yatashi. Research methods used is a descriptive qualitative method. Which is the source. The data for this research are the head of the Madrasah, Deputy Head of Sarpras, Teachers and administration. The research results show that the management strategy educational facilities and infrastructure in improving quality learning has gone quite well. However, the existing strategy still exists infrastructure management has not yet run optimally. Deep advice In this case, the head of the madrasah must take a firm policy for management of facilities and infrastructure, apart from that teachers and students must also have the awareness to maintain existing facilities and infrastructure so that it can continue to have use value and be able to improve quality of learning in madrasas